O devido processo legal e a inelegibilidade por rejeição de contas de gestão - Lourenço, Cleide Sodré (2022)
The study intends to answer the following research problems: Is the TCU accounting process, as it is developed, sufficient to support the adequate judgment of the ineligibility of managers who had their accounts judged irregular by the Electoral Justice? Does the articulation currently existing between the Federal Audit Court and the Electoral Justice, with regard to the decree of ineligibility of managers who had their accounts judged irregular, satisfy the normative parameters of due legal process or does it demand improvement? In light of the constitutional guarantees of the process, the articulated action between these institutions is compatible with the competences of the Courts of Auditors, the competence of the Common Justice to judge actions of improbity and the competence of the Electoral Court to examine the incidence of causes of ineligibility? The hypothesis is that the accounting process system does not seem to allow for the subsidy of sufficient elements for the measurement and determination of the practice of an act of improbity as a requirement for the declaration of ineligibility, even because such an investigation does not seem to be compatible with the constitutional powers of the Courts of Auditors. For that, the deductive methodology was adopted. The purpose of this research is to contribute specifically to the construction of knowledge involving the management accounts process, enabling its improvement with a view to protecting the fundamental rights involved.